Nursing ethics and the Holocaust: pilot of an innovation in teaching. Issue 2 (3rd April 2022) - Shields, Linda; Manning, Jennifer; McAllister, Margaret; O'Brien, Darren; Shields, Kirril; Emeto, Theophilus I.; Brien, Donna Lee; Murray, John; Benedict, Susan
ABSTRACT: More nurses than doctors killed in the Holocaust but are little studied. In Nazi 'euthanasia' institutional patients, with others, were killed by nurses. A German film, Fog in August (2016), tells of a boy caught in Nazi 'euthanasia'. We piloted the film to increase knowledge about nurses in Nazi 'euthanasia'. In Australia, 21 participants (health professionals, community members) completed pre-and-post questionnaires testing levels of knowledge. Knowledge increased – median post-score (1.75) > pre-score (1.0), median of differences 0.5 ( p = 0.001). This film effectively increased knowledge, and the study methods worked. We will develop a project to teach nurses about genocides.